Digital Transformations in Welfare: Artificial Intelligence and Social Services - Veraldi, Roberto; Fasciani, Chiara (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
In recent years, artificial intelligence has emerged as one of the most transformative technologies of our time, leading to a reorganization of social relationships and a restructuring of the Welfare System. This makes it necessary to rethink social policies and services for people with disabilities and other fragilities. This study aims to analyze the impact of AI on decision-making processes and on the actions of social workers, assessing both the benefits and the potential risks.